The fertility of recent immigrants to Canada - Alícia Adserà; Ana M. Ferrer (Institute for the Study of Labor (IZA), 2013)
In this paper we examine the fertility experience of immigrants during their first years in Canada. Fertility decisions at the time of arrival may be crucial in determining immigrants' economic assimilation into the new country, as households with infants usually face large expenses and are constrained in the amount of time they can supply to the labour market. Using the confidential files of the Canadian Census of Population for the years 1991 through 2006 we look at native born-immigrant differentials in new births up to five years after migration. We find evidence of a relatively rapid growth in births during this initial period compared to both similar natives and migrants themselves during the two years before the move. To what extent the presence of infants in immigrant households converges to the levels of the native-born during the early migration years differs greatly by broad area of origin.
Keywords: J11; J13; J15; 330; immigrant fertility; fertility disruption; recent immigrants; Canada